Histórias de adolescentes autores de atos infracionais institucionalizados em um Centro Socioeducativo de Roraima - Martins, Marília Ross dos Reis Pantoja (Universidade Federal de Roraima, 2018)
Based on interviews conducted with adolescents who were recidivists in the conduct of infractions and who were sentenced with a socioeducational measure in a closed environment, carried out in a unit of Boa Vista-RR, the present dissertation had as general objective: To analyze their life history. Its specific objectives were: (a) to identify factors that contributed to the practice of infractions and their recidivism; and (b) to know the dynamics of the Socio-Educational Unit and the evaluation they make of the assistance offered to them in complying with their measures as a process of re-socialization. Methodologically, the research was inspired by the Oral History of Life, and from the point of view of the procedure, open interviews were conducted, as well as field observation and data records of the institution. In terms of results, I highlighted as important factors: all adolescents interviewed stated that they suffered some kind of violence inside or outside the institution, one of them being living in very precarious financial conditions or extreme poverty; in addition, most of them before the hospital had already left the school environment and the abusive use of illicit drugs was a part of their lives. At the institution, these adolescents (who, since the age of 12, undergo processes of detention in a socio-educational environment) experienced punitive experiences, and for them the recuperative conception of the CSE / RR is repressive, that is, they consider that for the CSE / RR, the re-socialization process leads to repression. The results show that these adolescents present a life trajectory marked by violence, poverty, school failure, marginal social inclusion and that, for this reason, they seek recognition in the friendships and respect in the affective bonds that build in the trajectory of their criminal life. In view of the complexity and problems that this theme offered, through the interviewees' perspective, I sought an understanding of the role of the socio-educational institution of deprivation of liberty in Roraima and its symbolic elements and social phenomena that occur inside and outside its walls, institution.